Effect of Nesting and Swaddling on Sleep Duration of Preterm Neonate Hospitalized at Tertiary Care Centre of Eastern Nepal - Pahadi, Nirmala Kumari; Chaudhary, Ramanand; Karn, Basant Kumar; Yadav, Upendra (Journal of Karnali Academy of Health Sciences, 2026)
Background: All preterm neonates’ sleep is disturbed during hospitalization period due to various stressful environmental factors and human error and without focusing in individual developmental care. This impacts neonatal neurological development as well as normal growth resulting lifelong disabilities. Thus, modification of the environment by intervening developmental care could minimize the iatrogenic effect and neuro-developmental delay by decreasing stressful environment. This study was conducted to assess the effect of nesting and swaddling on sleep duration of preterm neonates during hospitalization at B.P.Koirala Instituted of Health sciences (BPKIHS).Methods: True experimental (post-test control design) study conducted among 36 preterm neonates, admitted in Nursery and Neonatal Unit of BPKIHS. Objective of this study was to assess effect of nesting and swaddling on sleep duration. Consecutive sampling technique was used for total sample size then after random allocation is applied for creates samples into two groups: experimental and control. Performa was used to collect sociodemographic characteristics. Sleep duration was recorded in self-administer observation form base on the observational behavior characteristics scoring of neonatal sleep by AASM (American Academy of sleep Medicine). Results: Among the enrolled neonates, there were 23 male (63.9%) and 13 female (36.1%) preterm. There was significant difference in sleep duration between experimental and control group. The mean ± SD of sleep duration was 59.22 ± 22.61 minute in experimental group and 39.50 ± 8.06 minute in control with p-value 0.001. Conclusions: Nesting and Swaddling can be used as convenient and effective method to increase neonatal sleep duration or rest period.